Concise Review: Guidance in Developing Commercializable Autologous/Patient‐Specific Cell Therapy Manufacturing. (7th October 2013) - Eaker, Shannon; Armant, Myriam; Brandwein, Harvey; Burger, Scott; Campbell, Andrew; Carpenito, Carmine; Clarke, Dominic; Fong, Timothy; Karnieli, Ohad; Niss, Knut; Van't Hof, Wouter; Wagey, Ravenska
Abstract : In this technical review, members of the International Society for Cell Therapy (ISCT) provide guidance in developing commercializable autologous and patient‐specific manufacturing strategies from the perspective of process development. Guidance is provided to help small academic or biotech researchers determine what questions can be addressed at the bench level in order to make their cell therapy products more feasible for commercial‐scale production. Abstract : Cell therapy is poised to play an enormous role in regenerative medicine. However, little guidance is being made available to academic and industrial entities in the start‐up phase. In this technical review, members of the International Society for Cell Therapy provide guidance in developing commercializable autologous and patient‐specific manufacturing strategies from the perspective of process development. Special emphasis is placed on providing guidance to small academic or biotech researchers as to what simple questions can be addressed or answered at the bench in order to make their cell therapy products more feasible for commercial‐scale production. We discuss the processes that are required for scale‐out at the manufacturing level, and how many questions can be addressed at the bench level. The goal of this review is to provide guidance in the form of topics that can be addressed early in the process of development to better the chances of the product being successful for future commercialization.